Possible Insulinotropic Action of Apolipoprotein A–I Through the ABCA1/Cdc42/cAMP/PKA Pathway in MIN6 Cells - Matsumura, Koki; Tamasawa, Naoki; Daimon, Makoto (Frontiers in Endocrinology, 2018)
Aims/Introduction: We studied the mechanisms for the possible insulinotropic action of apolipoprotein (Apo) A-I in mouse insulinoma (MIN6) cells. Materials and Methods: The effects of ApoA-I on cAMP production and glucose-stimulated insulin secretion (GSIS), and the dose dependency (ApoA-I at 5, 10, 25, and 50 µg/ml) were determined using MIN6 cells. The effects of the small‐interference ribonucleic acid (siRNA) of ATP‐binding cassette transporter A1(ABCA1) and Cell division control protein 42 homolog (Cdc42) on the insulinotropic action of ApoA-I was studied, as well as mRNA and protein levels of ABCA1 and Cdc42. Then, the influence of cAMP inhibitor SQ22536, and the cAMP-dependent protein kinase inhibitor Rp-cAMPS on ApoA-I action were studied. Results: Addition of ApoA-I produced cAMP and increased insulin secretion, dose-dependently in high glucose concentration (25 mmmol/l). and ABCA1 protein and Cdc42 mRNA and protein were also enhanced. Specific ABCA1 and Cdc42 siRNA significantly decreased the effects of ApoA-I on insulin secretion compared with negative controls. Manifestations of ABCA1 and Cdc42 mRNA and protein were less than that of the negative control group. Both cAMP inhibiror (SQ22536) and protein kinases inhibitor (Rp-cAMPS) strongly inhibited the effects of ApoA-I on insulin secretion. Conclusions: We demonstrated that ApoA-I enhances glucose-stimulated insulin release in high glucose at least partially through the ABCA1/Cdc42/cAMP/ Protein kinase A (PKA) pathway. Ethics statements (Authors are required to state the ethical considerations of their study in the manuscript, including for cases where the study was exempt from ethical approval procedures) Does the study presented in the manuscript involve human or animal subjects: No